Poor Adherence to Common Recommendations and Associated Factors among Outpatients with Type 2 Diabetes Mellitus in a Police Hospital of Ethiopia - Shimels, Tariku; Abebaw, Melesse; Gebretekle, Gebremedhin Beedemariam (Journal of Social Health and Diabetes, 2021)
Introduction Poor adherence to medication and healthy lifestyle managements, such as diet and regular exercise, remains to be a challenge for patients with type 2 diabetes mellitus. The objective of this study was to assess the pattern of adherence to common recommendations, reasons, and factors associated with poor overall adherence among outpatients with type 2 diabetes mellitus in a police hospital of Ethiopia.Method A facility-based cross-sectional study was done between 15 October 2016 and 15 January 2017. Systematic random sampling method was applied to recruit participants. A semistructured interview guide with an observation checklist was used to collect data. SPSS v.20.0 was used in the analysis.Results Out of 361 participants, over half (56.5%) participants were male and 235 (65.1%) participants were military. Nearly half (49%) of the participants were on oral combination therapy. Only 194 (53.7%) of the patients showed good adherence for diet. Half (50.1%) of the respondents had poor adherence to all recommendations. Reasons for poor adherence included lack of adequate knowledge (68.9%) for diet, carelessness (37.8%) for exercise, and lack of adequate knowledge (34.8%) followed by carelessness (28.3%) and forgetfulness (19.6%) for medication. Intake of herbal medicines doubled the likelihood of good adherence.Conclusion Adherence of patients to diet was found to be suboptimal. Lack of adequate knowledge, carelessness, and forgetfulness were among the reasons mentioned. Only use of herbal medicine showed statistical significance with adherence. Patient education on dietary practice is required in the study setting.
Keywords: Ethiopia; cross-sectional study; police hospital; poor adherence; type 2 diabetes mellitus